Structures Congress 2019 : buildings and natural disasters : selected papers from the Structures Congress 2019, April 24-27, 2019, Orlando, Florida - Soules, J. G. (American Society of Civil Engineers, 2019)
This collection contains 31 peer-reviewed papers on buildings and natural disasters presented at the Structures Congress 2019, held in Orlando, Florida, April 24-27, 2019.
Keywords: Structural engineering -- Congresses.; Structural analysis (Engineering) -- Congresses.; Geotechnical engineering -- Congresses.; elektronické knihy; electronic books